Strategi Pondok Pesantren Dalam Membangun Ketahanan Lembaga Berbasis Spiritualitas Tasawuf di Era Digital - Beril, Moh. Kholip Beril Arahman (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
This research explores Pondok Pesantren Darussalam's strategy in building institutional resilience based on Sufi spirituality amidst digital disruption. A descriptive qualitative approach was used, with data collection techniques including observation, documentation, interviews, and literature review, focusing on the perspectives of alumni students from Ma'had Aly Darussalam. The findings reveal four main strategic models: the study of the book Ihya' Ulumiddin, the establishment of Ma'had Aly Darussalam specializing in Tasawwuf wa Thariqatuhu, community service within the pesantren, and practicing sunnah fasting under the guidance of the pengasuh. The study of Ihya' Ulumiddin serves as a spiritual and moral foundation for students, fostering loyalty, maintaining moderation in religious understanding, and encouraging spiritual independence. The establishment of Ma'had Aly Darussalam is a concrete innovation to produce Sufi scholars and become a center for Sufi studies. Students' community service, both internal and external, strengthens the pesantren's image and alumni loyalty. The practice of sunnah fasting contributes to the development of disciplined character, self-control, and deeper spirituality. Furthermore, the pesantren utilizes digital technology for live streaming of book studies and events, expanding its missionary reach and strengthening community bonds. Thus, Pondok Pesantren Darussalam successfully integrates Sufi values with digital innovation, preserving tradition while remaining relevant and contributing in the modern era.